2016
DOI: 10.1016/j.pep.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and characterization of the recombinant cysteine-rich antimicrobial peptide snakin-1 in Pichia pastoris

Abstract: Snakin-1 (SN-1) is a small cysteine-rich plant antimicrobial peptide with broad spectrum antimicrobial activity which was isolated from potato (Solanum tuberosum).Here, we carried out the expression of a recombinant SN-1 in the methylotrophic yeast Pichia pastoris, along with its purification and characterization. A DNA fragment encoding the mature SN-1 was cloned into pPIC9 vector and introduced into P. pastoris.A large amount of pure recombinant SN-1 (approximately 40 mg/1L culture) was obtained from a fed-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…The native SN‐1 peptide from potato tuber was extracted and purified according to the procedures published previously with some modifications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The native SN‐1 peptide from potato tuber was extracted and purified according to the procedures published previously with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…SN‐1 is reported to possess significant activity against a wide range of both plant and human pathogens. Our recent report demonstrated that SN‐1 is a membrane‐active AMP that can kill targets by membrane disruption without being toxic to mammalian cells . According to X‐ray crystallographic analysis of SN‐1, its 3D structure is characterized by two short helices (α1 and α2) forming a helix‐turn‐helix, an additional helical section consisting of a short 3 10 ‐helix, two rigidly held loops, and six disulfide bonds between Cys 5 Cys 30 , Cys 9 Cys 26 , Cys 13 Cys 22 , Cys 29 Cys 62 , Cys 33 Cys 49 , and Cys 35 Cys 47 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Basic Local Alignment Search Tool algorithm, the identified peptides were evidenced in proteins of the snakin/GRP family from various plant species. One of them, the snakin-1 from potato, produced in recombinant form 4 and sharing 82.5% sequence identity with Pru p 7 and 79.4% with the GRP of Theobroma cacao (Fig 1, B), was tested in direct and inhibition western blots for its binding with serum IgE from CPAP. Out of 30 CPAP sera, all those expressing IgE to BP14 exhibited IgE reactivity to snakin-1 (n 5 15) (Fig 2 [F2-4/C] , A and B).…”
Section: To the Editormentioning
confidence: 99%
“…Similar fusion partners such as SUMO [258a,260a] are also used in this scenario, followed by enzymatic cleavage to release the native, active peptides. Other expression hosts used in peptide production include P. pastoris, which may be useful in producing cysteinerich AMPs [263] that fold poorly in E. coli, [264] B. subtilis to express an anti-Gram positive fungal plectasin fused to SUMO, [265] and rice leaves. [266] The main alternative to recombinant peptide expression is solid phase peptide synthesis (SPPS), which is now largely dominated by the fluorenylmethyloxycarbonyl (Fmoc) approach.…”
Section: Progress Reportmentioning
confidence: 99%